Neurohumoral mechanisms associated with orthostasis: reaffirmation of the significant contribution of the heart rate response - Convertino, Victor A. (Frontiers in Physiology, 2014)
The inability to compensate for acute central hypovolemia underlies the clinical development of orthostatic hypotension and instability (e.g., syncope). Although neuro-humoral control of both cardiac output and peripheral vascular resistance contributes to hemodynamic stability during orthostasis, a notion has been proposed that the failure of adequate peripheral vascular constriction rather than cardiac responses represents the primary mechanism the development of orthostatic intolerance. This review article provides an opportunity to present compelling evidence captured over the past 30 years in our laboratory to support the concept that neural-mediated tachycardia during orthostasis in healthy individuals represents a critical response to tolerating acute reduction in central blood volume in addition to, and independent of, peripheral vascular constriction. In this review paper, data are presented from experiments using graded lower body negative pressure (LBNP) as a method to induce orthostatic intolerance in two experimental human models: 1) comparison of heart rate and autonomic responses in individuals with relatively high and low tolerance to LBNP; and 2) vagal and sympathetic blockade of cardiac neural control. These experiments revealed that: 1) greater elevations in heart rate are associated with higher orthostatic (LBNP) tolerance; 2) higher orthostatic heart rate is associated with greater sympathetic nerve activity and withdrawal of vagally-mediated cardiac baroreflex response; and 3) nonspecific sympathetic blockade causes a pronounced reduction in heart rate and LBNP tolerance. Cardiac parasympathetic withdrawal contributes to protection against development of hypotension during the initial seconds of transition to an orthostatic challenge, while the primary mechanism by which tachycardia defends orthostatic stability in healthy subjects for extended durations is mediated predominantly through sympathetic adrenergic control.